Here and there a leaf - Heywood, Louise (Sherman, French & co., 1912)
No thought for to-morrow.--Bearing the cross.--He is coming.--Encouragement for the poor.--That it might be fulfilled.--Be patient now.--Our girls and boys.--Common sense in religion.--Our responsibility.--Settle it with Jesus.--Faith and works.--Not believing because not understanding.--No middle way.--Are we growing old?--The risen Christ.--The parting of the way.--Words of cheer for the aged.--Far from home.--The good fight.--Woman's high estate.--Tired mothers.--Dear Baby Ralph.--Home, sweet home.